Deconstructing the Diet of Young South Asians Socialized Within the United Arab Emirates: A Mixed-Methods Study Using Social Network Analysis. (14th June 2022) - Tan, Zhong Chen; Ali, Shahmir; Ansari, Suman; Brar, Ajay; Mohammed, Youmna; Merdjanoff, Alexis; Parekh, Niyati; Abdulle, Abdishakur; Jabari, Andrea; Ali, Raghib; DiClemente, Ralph
Abstract: Objectives: South Asians comprise most of the United Arab Emirates (UAE) population and face a complex non-communicable disease (NCD) burden linked with dietary behaviors. While past research has focused on disease risk factors of first-generation migrant workers, little is known on the dietary behaviors of the South Asians born or socialized within the UAE, who similarly face a growing NCD burden yet a distinct set of social forces relevant to health. Methods: 18–25-year-old UAE-based South Asians who spent at least 10 years of their life in the country were recruited via social media to participate in a mixed methods study. Participants first completed a survey to identify and rank factors contributing to their diet, including the strength (from 1 to 10) of the connection between different factors in jointly influencing eating behaviors. Descriptive and social network analysis (SNA) methods were used to analyze the factor data; all participants with contact details were invited for interviews to disentangle and interpret quantitative findings (analyzed using rapid qualitative analysis). Results: A total of 150 young UAE-based South Asians completed the survey (mean age 20.8, 78% female, 48% born in the UAE). Drivers with the highest overall and rank-adjusted saliency were family (130; 90.5), taste (120; 80.3), and cost (109; 65.8). Strong connections were made between ease of preparation and religion (10.0) as well as mood and culture (10.0) as diet-contributing factors. SNA revealed family to consistently be the most central factor (degree: 28, betweenness: 37.2, closeness: 0.03), followed by taste and cost. Of the 71 participants who provided contact details, 11 agreed to be interviewed. Participants interpreted the saliency of family in diet and health to reflect the disconnect experienced by the South Asian community with other facets of UAE society and noted school environment to be a particularly influential yet less prominent factor in the quantitative data. Conclusions: Findings provide specific, actionable considerations in the development of nutritional interventions tailored to the underserved, understudied population of South Asians socialized within the UAE, and pathways for further research to better understand these interconnected contributors to diet. Funding Sources: The NYU South Asian Health and Research Group (SAHARA).